PENERAPAN MODEL STUDENT FACILITATIR AND EXPLAINING DENGAN MEDIA POSTER UNTUK MENGURANGI MATHEMATIC ANXIETY SISWA - Devin Anggraeni Fitri; Ummu Sholihah (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2024)
Mathematics is a branch of science whose object of study is abstract in the form of symbols and shapes. The perception that emerged among the public said that only smart students (high learning outcomes) could master mathematics. However, what happens in the field is that the majority of students will experience anxiety when learning mathematics in the low to high category. Anxiety when learning mathematics is commonly called mathematical anxiety. This study used a quantitative approach with experimental method. The purpose of this study was to investigate the effect of cooperative learning model type Student Facilitator and Eksplaining (SFE) with poster media on students' mathematical anxiety. The population in this study were all students of class X MAN 3 Tulungagung. Two samples were selected by drawing lots. Learning with conventional methods was carried out in the control class, while the cooperative learning model of the Student Facilitator and Explaining (SFE) type with poster media was carried out in the experimental class. The results of data analysis showed that: (1) the average test of students' mathematical representation abilities in the control class was 73.2 while in the experimental class was 78.6; (2) the mathematic anxiety of students who learn using the Student Facilitator and Explaining (SFE) cooperative learning model with poster media is lower than the ability of the mathematical representation of students who learn with conventional methods; and (3) there is an influence of the Student Facilitator and Explaining (SFE) cooperative learning model with poster media on students' mathematical anxiety